Vespasian’s raids in the Jaffa region reconsidered - Arbel, Yoav (Journal of Jewish studies, 2024)
According to Josephus, raiding the countryside of conquered cities was a standard Roman practice during the suppression of the First Jewish Revolt (66-70 ce), intended both as an additional sanction and as a warning against future insurrections. Such punitive raids were reportedly carried out in the area around Jaffa, the only insurgent stronghold on the Mediterranean shore. Yet despite the clearly visible destruction layers in archaeological sites, decades of research and dozens of excavations in the vicinity of Jaffa yielded very few remains that can be linked to these raids. Analysis combining archaeological, historical and comparative data makes it possible to reassess the extent and intensity of the Roman raids in the area surrounding Jaffa, and by inference in other locations.